Effect of Implant Length on the Failure Rates of Dental Implants: An Umbrella Review - Yagthan Haider; Norehan Mokhtar; Husniyati Roslan; Jer Ooi Ping; Hamid Enezei (Dental Hypotheses, 2025)
Introduction We aimed to systematically examine outcomes of currently available systematic reviews and meta-analyses to assess the effect of implant length on the failure or success rates of dental implants in natural bone. Methods: The PICO framework was used for structuring clinical questions. Cochrane Database for Systematic Review, PubMed, Scopus, and Web of Science were searched via the following strategy: (dental implant* OR oral implant* OR osseointegrated implant* OR Dental Implantation) AND (“implant length” OR “length of implant") AND (systematic review OR meta-analysis). Risk of bias (quality) assessments were carried out using a measurement tool to assess systematic reviews. Data synthesis was done according to a method defined by Joanna Briggs Institute. Results: Study of Kotsovilis et al., which included 12 studies, suggested no significant difference in survival rates between short and long dental implants. In contrast, study of Ravidà et al., which included 66 studies covering 4525 implants, concluded that in the presence of sufficient natural bone, longer or regular-size dental implants are preferred to short implants in the posterior maxilla. Yet, in posterior mandible, short implants serve as a prudent alternative. Study of Abdel-Halim et al., which included 353 studies analyzing 25,490 short and 159,435 long implants (total: 184,925), concluded that short implants had a significantly higher risk of failure in comparison with long dental implants. Conclusion: While earlier research suggested no significant difference in survival rates between short and long dental implants, more recent studies indicated that short implants may exhibit a higher failure rate, especially in the posterior maxilla. However, with respect to methodological divergence, low quality, and lack of availability of raw data among included systematic reviews we cannot conduct an umbrella meta-analysis and reach to a definitive conclusion.